Embryology Update - Wu, Bin (IntechOpen, 2023)
Embryology is the study of the prenatal development of gametes (sex cells), fertilization, and development of embryos and fetuses. There have been many technological innovations and advancements in this field over the last decade, especially in in vitro fertilization (IVF). This book discusses these innovations and presents recent and relevant research. The chapters discuss gamete collection and freezing, how to improve IVF outcomes, embryo development, organogenesis of the early embryo, and much more.